Keluarga Buddhis Theravada Indonesia (KBTI): Urgensinya Mendukung Lembaga Pendidikan Formal Buddhis sebagai Nibaddha Kusala - Majaputera Karniawan; Sutrisno Sutrisno; Srie Muldrianto (Dhammavicaya : Jurnal Pengkajian Dhamma, 2024)
Since Dhammacakka (599BCE/528BCE) to its golden era (450-1193CE), the development of Buddhism cannot be separated from the role of the world of education, but the spirit of Buddhist support for the development of formal education is not sustainable in the 21st century. The phenomenon that occurs in Indonesia is that Buddhists build more places of worship (monasteries/cetiya/arama) than formal educational institutions with a percentage reaching 10:1000. This study aims to determine the perspective of the Indonesian Theravada Buddhist Family (KBTI) in seeing the importance of supporting formal Buddhist educational institutions as a field of empowerment that is continuously rewarding (Nibaddha Kusala). Qualitative methods with historical descriptive analysis and heuristics were chosen to find meaning in the form of historical data on the development of Buddhist education, then triangulated with data from interviews with KBTI member organizations. The results of this study indicate that all KBTI member organizations consider formal educational institutions to be an important thing to support, but there is still room for apathy and a lack of integration with each other in supporting formal Buddhist educational institutions.